The influence of internal marketing on customer buying decision: The case of Nyanza bottling company limited. - Mwakalukwa,Tulinagwe . (Mzumbe University, 2024)
A dissertation Submitted to Mzumbe University as a Partial fulfillment of the requirement for the award Master’s Degree of Business Administration in Corporate Management (MBA-CM)